Development of Arabic Language Learning Media Based on Pop Songs to Enhance Students' Language Skills - Haryono, Abdullah Abdul; Ali, Mad (Abjadia : International Journal of Education, 2025)
Mastery of Arabic language is a crucial aspect of Arabic language proficiency, yet it is often perceived as difficult and unengaging by students. Therefore, innovative, contextual, and enjoyable learning media are needed. This study aims to develop and determine the effectiveness of a learning medium based on the Book of Translated Pop Songs(Indonesian–Arabic) in enhancing students’ Nahwu skills. his research uses the Research and Development (RD) method following the Borg and Gall development model, which includes needs analysis, product design, product development, field testing, product revision, and validation testing. Expert validation was conducted to assess the feasibility of the media, while trials were carried out with students of MTs Al-Ihsan Pondok Pesantren Al-Ihsan Air Rumbai, Muko-Muko. Research instruments included pre-tests and post-tests to measure students' improvement in understanding Nahwu. The pre-test results showed an average student score of 63.33%. After the implementation of the Book of Translated Pop Songs, all 30 students scored above the Minimum Mastery Criterion (KKM) of 75. There was a 29.60% improvement in Nahwu proficiency. Additionally, the majority of students responded positively to the learning medium. Learning media based on contextually translated pop songs have been proven to enhance student interest and understanding in Nahwu learning. This approach can serve as an alternative for Arabic language teachers to create a more engaging and meaningful learning environment. The Book of Translated Pop Songs (Indonesian–Arabic) has proven to be an effective learning medium in improving students’ mastery of Arabic Language and contributes positively to their learning engagement.